Teknik Stenografi dengan Menggunakan Metode Visual Attacks dan Statistical Attacks - Fuad, Nurul; -, Suyono; Setyati, MT, Ir. Endang (Jurnal Ilmiah Teknologi Informasi Asia, 2011)
Data security is the main point to keep the confidentiality of information, specifically the data which contain of sensitive information that should be known by the eligible one. Furthermore, when on line system(network system) is used to deliver, thus if the data is not protected before it will have any risk. One of the ways used to secure data is by using Steganography system. Thereare some methods of steganographic that utilized a large amount of confidential informations in the pixels of the cover image. Pseudonym used by the majority of steganography tools fundamentally have some weaknesses in confidentiality communication. Then, attack development is used to overcome with the weaknesses of steganographic algorithm in case of assessing security system. There are two kinds of attacks that can be used, namely Visual and Statistical Attacks. Visual attacks, to explain the difference between noise and visual patterns, while the statistical attacks to detect steganographic method which is used.